A formação docente em serviço: uma experiência fundamentada na educação jesuítica - Trigueiro, Danieli de Sousa (Universidade do Vale do Rio dos Sinos, 2021)
The present study addresses teacher training, in view of the changes and challenges that arise in our society, with the school being a place of interaction and human formation. The goal of this research was to investigate in-service teacher training and its consequences, from the perspective of Jesuit Education, with a view to contribute to the integral formation of the student. Two philanthropic schools, with 100% free of charge, belonging to the Jesuit Education Network, located in the municipality of Teresina, in the state of Piauí, were taken as the locus of this research. In order to meet the objective the research, was guided by the following research question: how in-service teacher training, based on Jesuit Education, favors the integral formation of the student, having as a cut the 1st cycle of Elementary School. As a methodology, it was a qualitative research, which was structured from three elements: the structured questionnaires with open and closed questions, applied to the teachers of the two school units; the study of documents - Common Educational Project of the Jesuit Education Network and the Political-Pedagogical Projects of both schools; and content analysis. We based our study on author as, Klein, Tardif, Alarcão e Nóvoa, were preferably used. The results indicated that inservice training favors the professional improvement of teachers, in some areas, being identified, from the analysis of the data, narratives, which start from what strengthen the ideas of Ignatian Pedagogy, although there has not been evidence of an understanding theoreticalparadigm from the answers to the questionnaires. Therefore, as a possibility of intervention, Conversation Circles were proposed to be developed with teachers during the period of the 2022 pedagogical journey.
Keywords: Formação docente em serviço; Educação Jesuítica; Formação integral; In-service training; Jesuit Education; Comprehensive training; ACCNPQ::Ciências Humanas::Educação